PENILAIAN KINERJA DAN KOMITMEN DALAM ETIKA PEMERINTAHAN - Ponijan, Ponijan (MAJALAH ILMIAH WIDYA, 2012)
The performance appraisal is a formal system to check, periodically review and evaluate oneâs performance, which is used toimprove performance, compensation adjustment, placement decisions, training, and development needs, career planning anddevelopment. The purpose of this paper is to discuss the way how to improve quality and quantity of the human resources in orderto achieve the corporate maximum performance. The method used is the library research and tha collected data is analyzed descriptively.It can be concluded that the assessment of performance and ethics is a doctrine of government administration in the form of GoodGovernance, especially on the use of power or authority in accordance with the values associated with the virtue of human nature.